2015
DOI: 10.1016/j.jdiacomp.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early relapse to insulin dependence in unprovoked A-β+ ketosis-prone diabetes

Abstract: Objective Unprovoked “A-β+” Ketosis-Prone Diabetes (KPD), a unique diabetic syndrome of adult-onset, obesity and proneness to ketoacidosis, is associated with rapid recovery of β cell function and insulin-independence. Whereas most patients experience prolonged remission, a subset relapses early to insulin dependence. We sought to define factors associated with early relapse. Methods We utilized a prospective, longitudinal database to analyze 50 unprovoked A-β+ KPD patients with ≥2 measurements of β cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Only 5%-10% of diabetic patients do not produce insulin because of complete destruction in pancreatic β-cells that results in hyperglycemia and ketoacidosis in type-1 diabetic patients (Gaba et al 2015). Type 2 diabetes (T2D), a non-insulin-dependent diabetes mellitus, is associated with insulin resistance as cells of the body can't respond to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Only 5%-10% of diabetic patients do not produce insulin because of complete destruction in pancreatic β-cells that results in hyperglycemia and ketoacidosis in type-1 diabetic patients (Gaba et al 2015). Type 2 diabetes (T2D), a non-insulin-dependent diabetes mellitus, is associated with insulin resistance as cells of the body can't respond to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies in drug-naïve subjects with newly diagnosed type 2 diabetes unequivocally showed that initiation of triple hypoglycemic therapy with metformin, pioglitazone and glyburide (Lingvay, Legendre, Kaloyanova, et al, 2009) or exenatide (Abdul-Ghani, Puckett, Triplitt, et al, 2015 will maintain A1C below 6.5% and be safe when prescribed for 3 years. What Gaba et al (2015) also emphasized in their report is that β-cell reserve is diminished by 2-fold in "A − β+" KPD patients who relapsed during the first year of remission. Therefore, another strategy to mitigate risk of relapse could include early and continuous use of insulin therapy even during time of remission.…”
mentioning
confidence: 80%
“…In keeping with this most sacred physician duty, the report by Gaba et al (2015) widens our horizons in helping us to deliver better care for KPD patients. The authors broaden our knowledge of KPD pathophysiology, but the results of this and other studies also do emphasize that there are too many who will relapse.…”
mentioning
confidence: 97%
See 2 more Smart Citations